Historical narratives of global modern art
1 online resource
Keywords: "Diversifying the current art historical scholarship, this edited volume presents the untold story of modern art by exposing global voices and perspectives excluded from the privileged and uncontested narrative of "isms." This volume tells a worldwide story of art with expanded historical narratives of modernism. The chapters reflect on a wide range of issues, topics and themes that have been marginalized or outright excluded from the canon of modern art. The goal of this book is to be a starting point for understanding modern art as a broad and inclusive field of study. The topics examine diverse formal expressions, innovative conceptual approaches and various media used by artists around the world and forcefully acknowledge the connections between art, historical circumstances, political environments and social issues such as gender, race and social justice. The book will be of interest to scholars working in art history, imperial and colonial history, modernism, and globalization"--